The Impact of Boycott Sentiment on Returns and Risk in Consumer Sector Stocks - Nurhayati, Immas; Suharti, Titing; Hurriyaturrohman, Hurriyaturrohman (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The purpose of this study is to examine the impact of product boycott sentiment on the returns and risks of six stocks in the consumer sector listed on the Indonesia Stock Exchange. The six stocks are UNVR, FAST, MAPI, MAPA, MAPB, and PZZA. The results show that PZZA experienced the highest decline in returns of -362.84%, followed by FAST at -303.91%, UNVR at -221.65%, MAPB at -180.84%, and MAPA at -72.09%. The only stock that experienced an increase in returns was MAPI at 88.09%. Based on the risk proxied by variance, FAST experienced a fairly high variance rotation from 0.00031 to 0.00175. UNVR, MAPA, and MAPB showed a decrease in variance, indicating a calmer market despite their negative performance returns. PZZA was the only company with stable risk but significantly negative returns. MAPI was the only stock with positive returns and increasing variance. Based on the mean difference test, PZZA's p-value of 0.02695 (<0.05) indicates a positive and significant effect of the boycott on PZZA's declining returns. Other issuers, UNVR, FAST, MAPI, MAPA, and MAPB, were not statistically significant, having p-values ​​>0.05